Manganese Catalyzed Hydrogenation of Azo (N=N) Bonds to Amines. Issue 15 (2nd July 2021) - Das, Uttam Kumar; Kar, Sayan; Ben‐David, Yehoshoa; Diskin‐Posner, Yael; Milstein, David
Abstract: We report the first example of homogeneously catalyzed hydrogenation of the N=N bond of azo compounds using a complex of an earth‐abundant‐metal. The hydrogenation reaction is catalyzed by a manganese pincer complex, proceeds under mild conditions, and yields amines, which makes this methodology a sustainable alternative route for the conversion of azo compounds. A plausible mechanism involving metal‐ligand cooperation and hydrazine intermediacy is proposed based on mechanistic studies. Abstract :